Impact of Virtual Interviewing on Time and Financial Costs for NRMP© Applicants: Did Regional Campus Students Save More? - Tiffany Schwasinger-Schmidt; Tessa Rohrberg; Anne Walling; Kari Nilsen (Journal of Regional Medical Campuses, 2021)
Background and Objectives: The sudden change from in-person to remote interviews by the National Residency Matching Program© (NRMP©) in 2020 was expected to result in significant financial and time savings for applicants. This project aimed to compare savings before and after the 2020-2021 interviewing season reported by students graduating from our institution’s regional and main campuses.